Güncel Periodontoloji Çalışmaları III (Bahar) - Gürbüz, Ezgi; Kaçar, Zeki; Karabıyık, Damla Kan; Kavruk, Fatma; Önder, Yasemin Beliz; Altındal, Dicle; Saraç Atagün, Özlem; Çetin Özdemir, Eda; Bilen, Emrah; Dursun Zahitovic, Hamide; Bıyıkoğlu, Başak; Tekin, Tümer; et al. (Academician Publishing Book DOI Portal, 2024)
-